Environmetal and technology externalities: Policy and investment implications - Atanas Kolev; Armin Riess (EIB Papers, 2007)
Recognising that environmental and technology externalities affect the development of renewable energy technologies, this paper illustrates how environmental policies induce technological change and how market failures that hinder technological progress weaken the impact of environmental policies on technological change; examines the rationale for and type of policies in support of renewables at an early stage of their commercialisation; analyses to what extent so-called experience curves enlighten the debate on the rationale of such policies; and - assuming that early-stage renewables cannot establish themselves in the market - develops a method for assessing the economics of renewable energy projects based on new technologies.
Keywords: 330; Förderung regenerativer Energien; Umweltpolitik; Technischer Fortschritt